Handbook on Forms of Employment - United Nations Economic Commission for Europe (United Nations, 2022)
The Handbook presents a broad framework to classify and understand forms of employment, which is centered around two main dimensions: work relationships (as defined in the 2018 International Classification of Status in Employment) and work modalities (the way in which work is coordinated, performed, and compensated). To develop a full understanding of forms of employment, the Handbook provides definitions of the concepts of permanence and stability of employment. It also covers the broader context of forms of employment which includes person-level circumstances, social protection, and quality of employment to help better understand the impact of forms of employment on well-being. The Handbook provides definitions of key concepts, general principles and guidelines as well as a list of key recommended indicators with the goal of facilitating national statistical efforts to classify, measure and track diverse forms of employment relevant to their national context.